2007
DOI: 10.4152/pea.200804315
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic Stripping Voltammetric Determination of Losartan in Bulk and Pharmaceutical Products

Abstract: Cathodic stripping voltammetric determination of losartan using hanging mercury drop electrode HMDE was described. The method was based on adsorptive accumulation of the species at HMDE and at pH 7, followed by alternating current AC sweep. The behavior of adsorptive stripping response was studied under various experimental conditions, e.g. type of supporting electrolyte, pH, accumulation time, scan rate and mode of sweep (direct current DC, differential pulse DP, square wave SW and AC). In Britton-Robinson bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…22 On the other hand, the N=N group in most organic compounds is known to be reduced much easier than C=N one. [23][24][25] So, considering the reduction potentials of irbesartan over the entire pH range, the reduction behavior of irbesartan on HMDE may be attributed to saturation of the azomethine group C=N in tetrazolyl moiety of irbesartan molecule 26 not to the N=N group which is in contradictory to that reported in literature.…”
Section: Electroreduction Of Irbesartancontrasting
confidence: 62%
“…22 On the other hand, the N=N group in most organic compounds is known to be reduced much easier than C=N one. [23][24][25] So, considering the reduction potentials of irbesartan over the entire pH range, the reduction behavior of irbesartan on HMDE may be attributed to saturation of the azomethine group C=N in tetrazolyl moiety of irbesartan molecule 26 not to the N=N group which is in contradictory to that reported in literature.…”
Section: Electroreduction Of Irbesartancontrasting
confidence: 62%
“…Habib et al [25] described a cathodic stripping voltammetric determination of losartan using hanging mercury drop electrode (HMDE). The method was based on adsorptive accumulation of the species at HMDE and at pH 7, followed by alternating current (AC) sweep.…”
Section: Voltammetric Methodsmentioning
confidence: 99%
“…Potentiometric method offers a simple system and cost effective method than that of other methods which are having high cost, multiple steps and time consuming. Habib et al (2008) reported stripping voltammetry determination of VAL using a Hanging Mercury Drop Electrode (HMDE), was based on adsorptive accumulation of the species at HMDE followed by first harmonic alternating current AC stripping sweep at pH 6, the response was linear over the concentration range of 0.08-0.64 mg/mL with regression coefficient 0.999 [92].…”
Section: Potentiometric Methodsmentioning
confidence: 99%